The Association between PARP1 and LIG3 Expression Levels and Chromosomal Translocations in Acute Myeloid Leukemia Patients - Hossein Pashaiefar; Marjan Yaghmaie; Javad Tavakkoly-Bazzaz; Seyed Hamidollah Ghaffari; Kamran Alimoghaddam; Izadi Pantea; Ardeshir Ghavamzadeh (Cell Journal, 2018)
Objective Chromosomal translocations are among the most common mutational events in cancer development, especially in hematologic malignancies. However, the precise molecular mechanism of these events is still not clear. It has been recently shown that alternative non-homologous end-joining (alt-NHEJ), a newly described pathway for double-stranded DNA break repair, mediates the formation of chromosomal translocations. Here, we examined the expression levels of the main components of alt-NHEJ (PARP1 and LIG3) in acute myeloid leukemia (AML) patients and assessed their potential correlation with the formation of chromosomal translocations.